The science of fermentation: yogurt's role in creating healthy smoothies / Mohamad Azli Bin Razali ... [et al.] - Razali, Mohamad Azli; Din, Norrina; Zainol, Noorliza (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Fermentation, a captivating biological process, has been pivotal in the culinary world for centuries, giving rise to various delicacies. One such product is yogurt - a delicious and nutritious dairy product that finds its way into numerous recipes. This article delves into the intricate science of yogurt fermentation, examining its connection to ingredient transformation, the significance of microbes, and its contribution to the crafting of healthy smoothies. Transformation of Ingredients: The transformation of milk into yogurt involves a series of complex biochemical reactions. Through fermentation, specific bacterial strains metabolize lactose, generating lactic acid. This acidification process not only lowers the pH but also causes milk proteins to coagulate, imparting yogurt with its characteristic texture and tangy flavor. When incorporated into smoothies, yogurt enhances the blend with a creamy and velvety consistency (Ghosh, 2019; Moyano, 2020).